Development of novel magnetoliposomes containing nickel ferrite nanoparticles covered with gold for applications in thermotherapy - Rio, Irina S. R. (2020)
Multifunctional nanosystems combining magnetic and plasmonic properties are a promising approach for cancer therapy, allowing magnetic guidance and a local temperature increase. This capability can provide a triggered drug release and synergistic cytotoxic effect in cancer cells. In this work, nickel ferrite/gold nanoparticles were developed, including nickel ferrite magnetic nanoparticles decorated with plasmonic gold nanoparticles and core/shell nanostructures (with a nickel ferrite core and a gold shell). These nanoparticles were covered with a surfactant/lipid bilayer, originating liposome-like structures with diameters below 160 nm. The heating capacity of these systems, upon excitation with light above 600 nm wavelength, was assessed through the emission quenching of rhodamine B located in the lipid layer. The developed nanosystems show promising results for future applications in thermotherapy.